Meningkatkan Kemampuan Mengenal Lambang Bilangan Satu Sampai Lima Melalui Media Balok Angka Bagi Anak Tunagrahita Sedang Kelas VII di SLBN 1 Padang - Yurnalisma Yurnalisma; Fatmawati Fatmawati (Universitas Negeri Padang, 2018)
This study was to determine wheter the wooden number blocks can improve the ability to number one to five correctely for medium intellectual disabiliy in grade 7 of special school No. 1 Padang. The study is an experimental resarch with a single subject research (SSR) method and A-B-A desigh. The data analysis is in the from of visual analisys of graphis displays. Subject in this study were moderate medium intelectual disability. The targer behavior of this research is for the student to be able to recognize the numbers one to five correctly. The variable measurement was in the form of the percentage of the number of instrument items. The results show that the student’s ability to identify number from one ti five improved an intervention using wooden number blocks were perfomed.